The Effect Of The Card Short Learning Model And Learning Styles On Learning Outcomes In Fikih Subjects - Ryan Fahmi; Indra Prasetia; Amini Amini (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study aims to empirically examine the effect of applying the Card Sort learning model and student learning styles on learning outcomes in Fiqh at MAS Al Ishlahiyah Binjai. The study uses a quantitative approach with a quasi-experimental design and a post-test only control group design. The research was conducted in the odd semester of the 2025/2026 academic year with a population of all 55 students in class X at MAS Al Ishlahiyah Binjai, using a saturated sampling technique. Class X-1 with 25 students was designated as the experimental class that was given the Card Sort learning model treatment, while class X-2 with 25 students was designated as the control class that used conventional learning. The independent variables in this study were the Card Sort learning model and student learning styles, while the dependent variable was the learning outcomes in Fiqh, which were measured through a multiple-choice cognitive test (post-test) that had been tested for validity and reliability with a reliability coefficient of 0.705. Data analysis was conducted using descriptive statistics, Kolmogorov–Smirnov normality test, variance homogeneity test (Levene Test), and hypothesis testing using Independent Sample t-test and ANOVA with a significance level of 0.05. The results showed that the average learning outcome of the experimental class was 84.32, which was higher than that of the control class, which was 71.56. The data were normally distributed and homogeneous, and the hypothesis test results showed a significance value of 0.000 (Sig. < 0.05), so it can be concluded that the Card Sort learning model and learning style had a significant effect on the learning outcomes of Fiqh subjects at MAS Al Ishlahiyah Binjai.